유전정보에 대한 자기결정권과 특허 - 박영규; Young-gyu Park (지식재산연구, 2009)
「생명 윤리 및 안전에 관한 법률」 제5조는 “누구든지 자신이 생명과학기술의 적용대상이 되는 경우 생명윤리 및 안전에 관하여 충분한 설명을 들은 후 이에 관한 동의여부를 결정할 권리를 가진다”고 규정하고 있다. 또한 「생명공학분야 특허심사기준」은 「생명 윤리 및 안전에 관한 법률」에 의해 금지되는 행위 또는 연구 성과물에 관한 발명을 특허법 제32조에 규정된 공공의 질서 또는 선량한 풍속을 문란하게 하거나 공중의 위생을 해할 염려가 있는 발명으로 규정하고 있다. 하지만 여전히 유전정보에 대한 자기결정권의 침해가 특허의 부여에 어떠한 영향을 미치는지에 대해서는 명확하지 않다. 이에 본고는 유전정보의 개념, 유전정보 보호의 필요성, 유전정보에 대한 자기결정권과 특허와의 관계, 유전정보에 대한 자기결정권과 특허의 부여를 연계할 때 나타날 수 있는 문제점을 중심으로 논의를 전개하고 있다. 이를 통해 최종적으로 「생명공학분야 특허심사기준」과 같이 유전정보에 대한 자기결정권과 특허의 부여를 연계시키는 것은 타당하지 않고, 유전정보에 대한 자기결정권의 보호는 형법, 보건법, 개인정보 관련 보호법 혹은 기타 법률에 의해 보장되고 아울러 이러한 법률을 통해 해결되는 것이 타당하다는 결론에 이르고 있다. Kingdom of the Netherlands submits that the patentability of isolated parts of the human body provided for by Article 5(2) of the Directive reduces living human matter to a means to an end, undermining human dignity. Moreover, the absence of a provision requiring verification of the consent of the donor or recipient of products obtained by biotechnological means undermines the right to self-determination. Nor are the elements of the human body patentable table in themselves and their discovery cannot be the subject of protection. Only inventions which combine a natural element with a technical process enabling it to be isolated or produced for an industrial application can be the subject of an application for a patent. Thus, an element of the human body may be part of a product which is patentable but it may not, in its natural environment, be appropriated. Biotechnological inventions may derive from research on possibly thousands of blood or tissue samples, possibly pooled and almost certainly anonymous at the time of analysis. Ⅰ do not consider that it is reasonable to expect patent examiners to satisfy themselves that the chain of consent with regard to each sample is unbroken and evidenced. It is rather the responsibility of the medical or research staff taking the samples to ensure that consent is given. That responsibility, together with the form and scope of the consent, will be imposed by national regulations, codes of practices, etc. outside the patent area.